Novel methods for spatial prioritization with applications in conservation, land use planning and ecological impact avoidance. Issue 5 (25th February 2022) - Moilanen, Atte; Lehtinen, Pauli; Kohonen, Ilmari; Jalkanen, Joel; Virtanen, Elina A.; Kujala, Heini
Abstract: Spatial (conservation) prioritization integrates data on the distributions of biodiversity, costs and threats. It produces spatial priority maps that can support ecologically well‐informed land use planning in general, including applications in environmental impact avoidance outside protected areas. Here we describe novel methods that significantly increase the utility of spatial priority ranking in large analyses and with interactive planning. Methodologically, we describe a novel algorithm for implementing spatial priority ranking, novel alternatives for balancing between biodiversity features, fast tiled FFT transforms for connectivity calculations based on dispersal kernels, and a novel analysis output, the flexibility map. Marking by N the number of landscape elements with data, the new prioritization algorithm has time scaling of less than N log2 N instead of the N 2 of its predecessor. We illustrate feasible computation times with data up to billions of elements in size, implying capacity for global analysis at a resolution higher than 0.25 km 2, or close to 1‐ha resolution for a continent. The algorithmic improvements described here bring about improved capacity to implement decision support for real‐world spatial conservation planning problems. The methods described here will be at the technical core of forthcoming software releases.